Interações sociais mediadas pela atividade física na terceira idade - Silva, Luis Gustavo Maias da (2012)
As a result of advances in science and technology, humanity has witnessed a phenomenal increase in life expectancy, and in order to senior citizens be able to enjoy such longevity, maintaining a standard of acceptable quality of life, actions of social and physical activities have been showing very favorable. Within this context, this research aimed to understand, with theoretical support, perceived changes in living with elderly who practice physical activities, in order to contribute to the improvement of researches and actions that provide the best results for this population. Therefore, it was chosen to collect data on a group of students from the Centro Regional de Estudos e Atividades para Terceira Idade (CREATI), with the help of focus group technique, which aims to capture information through the interaction between participants. There were selected nine subjects (eight women and one man) aging between 63 and 78 years, having as criterion their attendance in workshops on physical activity for more than 10 years on a regular basis. The data was collected through interviews conducted under the guidance of three predetermined questions. The information obtained allowed to point out that the elderly interviewed experience the process of aging in different ways and describe aging a time of pleasure. There were not presented frustration, conflicts and other experience of drama in this period, so that were not identified sense of rejection and / or inferiority in view of changes and loss. Through the statements of the subjects, it was shown that social interactions mediated by physical activity contribute to the acceptance of themselves and others, leading to a positive view about the aging process and its implications